MOTIVASI KERJA DALAM PENINGKATAN KINERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH, PENELITIAN DAN PENGEMBANGAN KOTA PALANGKA RAYA: Work Motivation in Improving Employee Performance at Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Palangka Raya City - Pasaribu, Annisa; Mambang, Mambang; Nurhasanah, Nurhasanah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Work motivation is a faktor that encourages someone to carry out activities at work. This is very important because motivation supports human behavior so that they want to work hard and enthusiastically in achieving their goals. Work motivation as a determinant of organizational success, one of which aims to improve the performance of employees of Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Palangka Raya. The purpose of this study is to find out and describe how work motivation in improving the performance of Bappedalitbang Palangka Raya employees, what are the motivating and inhibiting faktors of work motivation in improving the performance employees of Bappedalitbang Palangka Raya City and what efforts are being made to increase work motivation of Bappedalitbang employees of Palangka Raya City. The method used in this research is qualitative method. In analyzing the research, the researcher used several data collection techniques through observation, interviews and documentation. In this study using the theory put forward by Afandi, namely through indikators of remuneration, working conditions, work facilities, work performance, recognition from superiors and the work itself. The results of this study indicate that work motivation in improving the performance of Bappedalitbang employees of Palangka Raya City has implemented the indikators proposed by Afandi. Work motivation in improving the performance of Bappedalitbang Palangka Raya employees is very good. However, further efforts are needed to further improve the performance of its employees.